2020
DOI: 10.1101/2020.09.04.20188045
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Computer-aided interpretation of chest radiography reveals the spectrum of tuberculosis in rural South Africa

Abstract: Background Computer-aided digital chest radiograph (CXR) interpretation can facilitate high-throughput screening for tuberculosis (TB), but its use in population-based screening has been limited. We applied an automated image interpretation algorithm, CAD4TBv5, prospectively in an HIV-endemic area. Methods Participants underwent CXR and, for those with symptoms or lung field abnormality, microbiological assessment of sputum collected at a mobile camp in rural South Africa. CAD4TBv5 scored each CXR on a 0-100 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 42 publications
1
17
0
Order By: Relevance
“…CAD4TB, Lunit INSIGHT CXR, and qXR's AUROCs in this study are slightly lower than those in previous independent evaluations. 17,26 Our subanalysis showed that the performance of computer-aided detection varied with demographic and clinical factors, as well as patient source, and therefore implied that variation exists in AI performance across different contexts and geographies. In our study population, rates of bacteriological positivity and rifampicin resistance are both higher than the national average because of the high proportion of referrals and urban population in this study.…”
Section: Discussionmentioning
confidence: 90%
“…CAD4TB, Lunit INSIGHT CXR, and qXR's AUROCs in this study are slightly lower than those in previous independent evaluations. 17,26 Our subanalysis showed that the performance of computer-aided detection varied with demographic and clinical factors, as well as patient source, and therefore implied that variation exists in AI performance across different contexts and geographies. In our study population, rates of bacteriological positivity and rifampicin resistance are both higher than the national average because of the high proportion of referrals and urban population in this study.…”
Section: Discussionmentioning
confidence: 90%
“…Our screening archive contained data from a variety of risk groups that are recommended for targeted TB screening given their high TB prevalence. Very few peer-reviewed studies have assessed the performance of CADs in such groups, and all studies except one (23) used earlier versions of CAD4TB (2426). Two of these studies suggested that CAD4TB v5 or v6 could achieve a similar performance as that of a trained field radiologist when interpreting CXRs of the Zambia National TB prevalence survey (25), or a senior radiologist when interpreting images from a population-based survey in a high HIV-endemic area in rural South Africa (23).…”
Section: Discussionmentioning
confidence: 99%
“…Several large-scale, community-based CXR screening initiatives have been recently implemented in high TB burden countries 6 11 . These programs show that this case finding approach is both feasible to implement in low- and middle-income countries (LMIC) and effective at identifying people with TB, particularly those with subclinical disease who are frequently missed by TB programs or only diagnosed after long delays 12 .…”
Section: Introductionmentioning
confidence: 99%
“…The majority of the published literature on CAD software for TB screening has focused on Delft Imaging’s CAD4TB (The Netherlands), which was one of the first commercially available CAD solutions 8 , 11 , 20 23 . Two systematic reviews, conducted in 2016 and 2019, also primarily included studies evaluating various versions of the CAD4TB software 24 , 25 .…”
Section: Introductionmentioning
confidence: 99%